Fluorescence enhancement of radix angelica dahurica by binding to single silver sphere - 王青如 史强 李淑红 王文军 (Chinese physics B, 2015)
We present a theoretical study of the influence of a single silver sphere on the fluorescence of radix angelica dahurica, which is a kind of traditional Chinese medicine. The enhancement factors of the excitation and the relaxation processes are deduced. The excitation can be enhanced more than 100 times at 315 nm. The enhancement factor of the emission can reach up to 9 at a center wavelength of 400 nm.